Screening of Marine Bacteria Capable of Degrading Various Polyaromatic Hydrocarbons - Elvi Yetti; Ahmad Thontowi; Yopi Y; Puspita Lisdiyanti (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
This research aims to screen and to identify marine bacteria able to degrade Polyaromatic Hydrocarbons (PAHs). 7 bacterial isolates were screened for the ability to degrade 6 PAHs (phenanthrene, naphthalene, dibenzothiophene, fluorene, phenothiazine, and pyrene). This screening step was conducted by sublimation method, in which the color change or clear zone appearance was used as an qualitative indicator to show the capability of the selected isolate to degrade PAHs. Two bacterial isolates, designated as LBF-1-0102 and LBF1-0103, showed capability in degradating the PAHs tested. In particular, the isolate LBF-1-102 was potential in degrading phenanthrene, naphthalene, dibenzothiphene, fluorene, phenothiazine, and pyrene.The isolate LBF-1-0103 showed the ability in degrading 2 (two) PAHs, i.e. dibenzothiophene and fluorene. Based on partial 16S rDNA analysis, LBF-1-0102 and LBF-1-0103 were identified as Pseudomonas balerica and Brachybacterium sp., respectively.